Enhanced Energy‐Storage Properties and Good Temperature Stability in 0.92(Sr0.7Bi0.2)TiO3–0.08Bi(Mg0.5Hf0.5)O3 Relaxor Ferroelectric Ceramic. Issue 6 (8th March 2021) - Kong, Xi; Yang, Letao; Cheng, Zhenxiang; Zhang, Shujun
Abstract : Herein, the (1 − x )(Sr0.7 Bi0.2 )TiO3 – x Bi(Mg0.5 Hf0.5 )O3 (SBT–100 x BMH, x = 0.04–0.10) relaxor ferroelectric ceramics are fabricated via the high‐temperature solid‐state reaction method. Dielectric and ferroelectric measurements reveal a typical relaxor characteristic with diffused and frequency‐dependent dielectric peaks. The characteristic Weibull breakdown strength (BDS) of 470 kV cm −1 with satisfied reliability is obtained by DC breakdown measurement. A maximum recoverable energy density of 3.5 J cm −3 with the corresponding energy efficiency of 92% is simultaneously achieved at 380 kV cm −1 . The recoverable energy density exhibits minor degradations from ambient temperature to 200 °C with variation below 20%, whereas the energy efficiency is maintained above 90%. In addition, the SBT–8BMH ceramic possesses a fast charge–discharge speed with high discharge power density of 2.9 MW cm −3 . All the results make this lead‐free relaxor ferroelectric ceramic a promising potential candidate for high‐temperature energy‐storage capacitor applications. Abstract : 0.92(Sr0.7 Bi0.2 )TiO3 –0.08 Bi(Mg0.5 Hf0.5 )O3 relaxor ceramic exhibits a high recoverable energy‐storage density of 3.5 J cm −3 and high energy efficiency of 92% at 380 kV cm −1 . Of particular importance is that it maintains the high energy efficiency (>90%) up to 200 °C, which makes it suitable for energy‐storage capacitors working under a high‐temperature environment.